Impact of aircraft noise on health - Benz, S.; Kuhlmann, J.; Jeram, S.; Bartels, S.; Ohlenforst, B.A.; Schreckenberg, D. (Springer, 2022)
Aircraft noise exposure is an environmental stressor and has been linked to various adverse health outcomes, such as annoyance, sleep disturbance, and cardiovascular diseases. Aircraft noise can trigger both psychological (annoyance and disturbance) and physiological stress responses (e.g. activation of the cardiovascular system and release of stress hormones). People are usually able to deal with this kind of stressor. However, a constant exposure to aircraft noise can cause a continuous state of stress. This in turn can constrain a person’s ability to regenerate and restore its resources to cope with the noise situation. As a consequence, the risk for certain negative health outcomes can be increased. Within the ANIMA project, literature reviews on the effects of aircraft noise on health outcomes have been performed. This chapter gives an overview of the relevant health outcomes affected by aircraft noise and summarises the results of different reviews and studies on these outcomes. Additionally, the underlying mechanisms of how noise impacts health are explained for daytime as well as night-time aircraft noise exposure (i.e. while sleeping). Further, the relevance of considering not only the general population, but vulnerable groups as well (such as children and elderly people) is described. Lastly, open questions for further studies are presented and discussed.